THE NUMERICAL SIMULATIONSTUDY SPANNING THE CONTINUUM/ATOMS SCALEON THE TYPE Ⅰ EDGE CRACK PROPAGATION PROCESS IN SINGLE CRYSTAL SILVERBASED ON THEDISPLACEMENT CONNECTION - SONG Kun; WANG LuSheng; LIU Bo; DING Jun; HUANG Xia; HE XiaoJin (Jixie qiangdu, 2018)
The study on deformation and failure mechanism of materials,and the progressof NEMS/MEMStechnology and biotechnologypromote the development of multi-scale analysis method. However,Multi-scale connectionisthe key of multi-scale model. The finite element method（ FEM） and molecular dynamics simulation（ MD） were combined to simulate the multi-scale models,and the stress intensity factors（ SIF） and displacement mechanics parameters were adopted to connect and convertthecontinuum region and discrete molecular dynamics region,then three multi-scale model of two-dimensional silver crack propagationwasestablished to obtain the crack tip trajectory and the micro-scale crackpropagationprocess. The result is in good agreement with theory and experiment,and proves the rationality of the method.